Q: If $5,000 is invested at 6% interest, how much money must be invested at 8% interest so that the total interest from the two investments is $660 after one year?
$4,500
$4,000
$5,500

A: 400 is 60.60% of 660.

xramen135@aol.com|Points 590|

Question

Asked 6/22/2011 1:06:50 PM

0 Answers/Comments

Rating

There are no new answers.

Solve 2x - 8 User: x + 17 = -3 **Weegy:**
x + 17 = -3
x = -3 - 17
x = -20 (More)

Question

Expert Answered

Updated 6/21/2015 1:10:52 PM

1 Answer/Comment

2x - 8 < 7

2x < 7 + 8

2x < 15

x < 15/2

2x < 7 + 8

2x < 15

x < 15/2

Added 6/21/2015 1:10:52 PM

This answer has been confirmed as correct, not copied, and helpful.

Solve the following system of equations.
2x + y = 3
x = 2y - 1

Question

Expert Answered

Updated 1/4/2015 10:50:10 PM

2 Answers/Comments

2x + y = 3

x = 2y - 1

substitute x in the first equation:

2(2y - 1) + y = 3

4y - 2 + y = 3

5y = 3 + 2 = 5

y = 5/5 = 1

x = 2(1) - 1 = 2 - 1 = 1

The solution for the system 2x + y = 3 x = 2y - 1 is (1, 1)

x = 2y - 1

substitute x in the first equation:

2(2y - 1) + y = 3

4y - 2 + y = 3

5y = 3 + 2 = 5

y = 5/5 = 1

x = 2(1) - 1 = 2 - 1 = 1

The solution for the system 2x + y = 3 x = 2y - 1 is (1, 1)

Added 1/4/2015 10:48:27 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [1/5/2015 11:24:26 AM]

2x + y = 7 (equ. 1)

y - x = 1 we can get x - y = -1 (equ. 2)

adding up equations 1 and 2 the result is:

3x = 6

x = 6/3 = 2

y = x + 1 = 2 + 1 = 3

The solution for the system 2x + y = 7 y - x = 1 is (2, 3)

y - x = 1 we can get x - y = -1 (equ. 2)

adding up equations 1 and 2 the result is:

3x = 6

x = 6/3 = 2

y = x + 1 = 2 + 1 = 3

The solution for the system 2x + y = 7 y - x = 1 is (2, 3)

Added 1/4/2015 10:50:10 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [1/5/2015 11:28:41 AM]

Find the quotient.
(4ab - 8a 2 + 12ac) ÷ 4a **Weegy:** 5a+10b=25c **User:** Find the quotient.
(6x 2 + 23x + 20) ÷ (5 + 2x) **Weegy:** x = -4/3 **User:** Simplify the expression.
3(2y - 8) - 2y(5 - y) **Weegy:** The simplify answer for this problem is x to the second power/4 -y to the second power **User:** Divide x 4 + 7 by x - 3.
A.3x 3 + 3x 2 + 9x - 27 R88
B.3x 3 + 3x 2 + 9x + 27 R88
C.x 3 + 3x 2 + 9x + 27 R88 **Weegy:** A.4 - 7x = 15 **User:** no its x 3 + 3x 2 + 9x + 27 R88 (More)

Question

Expert Answered

Updated 6/30/2014 9:06:34 AM

3 Answers/Comments

Find the quotient. (4ab - 8a^2 + 12ac) ÷ 4a

=(4ab-8a2+12ac)/(4a)

=(4b-8a+12c)/4

=b-2a+3c

=(4ab-8a2+12ac)/(4a)

=(4b-8a+12c)/4

=b-2a+3c

Added 6/30/2014 9:02:53 AM

This answer has been confirmed as correct, not copied, and helpful.

Select the correct difference.
-3z 5 - (-7z 5)

Question

Not Answered

Updated 8/13/2014 8:23:00 AM

1 Answer/Comment

-3z^5 - (-7z^5)

=-3z^5+7z^5

=-z^5+-z^5+-z^5+z^5+z^5+z^5+z^5+z^5+z^5+z^5

=z^5+z^5+z^5+z^5

=4z^5

=-3z^5+7z^5

=-z^5+-z^5+-z^5+z^5+z^5+z^5+z^5+z^5+z^5+z^5

=z^5+z^5+z^5+z^5

=4z^5

Added 8/13/2014 8:23:00 AM

This answer has been confirmed as correct, not copied, and helpful.

27,038,127 questions answered

There are no comments.